The Relationship Between the Marketing Mix and the Volume of Furniture Sales in Kendari City - Marfuatun, Marfuatun; Salam, Idrus; Zani, Munirwan (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This research aims to determine the marketing mix used by furniture industry owners in marketing furniture in Kendari City and determine the relationship between the marketing mix and the volume of furniture sales in Kendari City. The population in this study is all furniture industries in Kendari City that are officially registered with the Kendari City Labor and Industrial Office, with 23 furniture industries. Based on field search results, the number of furniture industries found in the field only amounted to seven furniture industries, so the determination of samples in this study using census methods by taking seven furniture industries as research samples. Variables in the study were respondents' identities (age, education level, and experience of effort), marketing mix (product, price, place, promotion, people, physical evidence, and process), and sales volume. Data analysis uses descriptive analysis and Spearman correlation analysis. The results showed that the marketing mix used by furniture industry owners in marketing furniture products in Kendari City had not been applied to the maximum, namely on promotional components, people, and physical evidence. The relationship between the marketing mix and furniture sales volume shows a significant and robust relationship, especially in product components, prices, places, people, and processes. The promotional component and physical evidence showed a weak relationship with furniture sales volume.